2017
DOI: 10.1038/srep41995
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of acrylamide carcinogen in Arabic coffee Qahwa, coffee and tea from Saudi Arabian market

Abstract: The present work describes the outcomes of the assessment on acrylamide contents in a number of thermally treated foods (Arabic coffee Qahwa, coffee and tea) obtained from the Saudi Arabian markets. A total of 56 food samples of different brands and origin were studied, the amounts of acrylamide in Arabic coffee Qahwa, coffee and tea were obtained in the range of 10 to 682 μg kg−1. In comparison to coffee (152–682 μg kg−1), the Arabic coffee Qahwa (73–108 μg kg−1) and tea (10–97 μg kg−1) contain lower amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Alternative defatting processes to the use of nonpolar organic solvent and SPE include the use of Carrez I and II solutions (Asnaashari, Esmaeilzadeh Kenari, Farahmandfar, Taghdisi, & Abnous, 2018; Khan et al., 2017; NegoiţĂ & Culeţu, 2016; Oroian, Amariei, & Gutt, 2016; Raters & Matissek, 2018; Razia et al., 2016; Yadav, Chhillar, & Pundir, 2018). Carrez I contains a 15% (w/v) solution of potassium hexacyanoferrate (II) trihydrate (K 4 [Fe(CN) 6 •3H 2 0), while Carrez II contains a 30% (w/v) solution of zinc sulfate heptahydrate (ZnSO 4 •7H 2 0) (Emdmillipore, 2013).…”
Section: Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative defatting processes to the use of nonpolar organic solvent and SPE include the use of Carrez I and II solutions (Asnaashari, Esmaeilzadeh Kenari, Farahmandfar, Taghdisi, & Abnous, 2018; Khan et al., 2017; NegoiţĂ & Culeţu, 2016; Oroian, Amariei, & Gutt, 2016; Raters & Matissek, 2018; Razia et al., 2016; Yadav, Chhillar, & Pundir, 2018). Carrez I contains a 15% (w/v) solution of potassium hexacyanoferrate (II) trihydrate (K 4 [Fe(CN) 6 •3H 2 0), while Carrez II contains a 30% (w/v) solution of zinc sulfate heptahydrate (ZnSO 4 •7H 2 0) (Emdmillipore, 2013).…”
Section: Extraction Methodsmentioning
confidence: 99%
“…Defatting with either nonpolar organic solvent efficiently solubilizes fats and oils, permitting easy removal of the F I G U R E 3 Sequence of steps for acrylamide extraction from food and analyte analysis by LC-MS or GC-MS solvent by reduced pressure evaporation to allow isolation of fat or oil content. Alternative defatting processes to the use of nonpolar organic solvent and SPE include the use of Carrez I and II solutions (Asnaashari, Esmaeilzadeh Kenari, Farahmandfar, Taghdisi, & Abnous, 2018;Khan et al, 2017;NegoiţĂ & Culeţu, 2016;Oroian, Amariei, & Gutt, 2016;Raters & Matissek, 2018;Razia et al, 2016;Yadav, Chhillar, & Pundir, 2018). Carrez I contains a 15% (w/v) solution of potassium hexacyanoferrate (II) trihydrate (K 4 [Fe(CN) 6 •3H 2 0), while Carrez II contains a 30% (w/v) solution of zinc sulfate heptahydrate (ZnSO 4 •7H 2 0) (Emdmillipore, 2013).…”
Section: Food Matricesmentioning
confidence: 99%
“…ACR is extensively-used as an additive in molecular laboratories, chemical engineering, water purification, mining, textiles, paper manufacturing, cosmetics and protein electrophoresis (Riboldi et al, 2014;Tepe and Çebi, 2019). Natural sources of ACR have been reported recently comprising drinking water, tobacco smoke, Arabic coffee (Qahwa), coffee, tea besides occupational exposure (Khan et al, 2017). ACR has been recorded to be toxic to nervous system (Seale et al, 2012;Nassar, 2017), reproductive system (Favor and Shelby, 2005;Ma et al, 2011) and precancerous to laboratory animals (Hogervorst et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hb Adducts from acrylamide and glycidamide can be quantified to measure the level of human exposure to acrylamide (Wenzl et al, 2003). ()() Epidemiological evidence on the relation between dietary acrylamide and the risk of several cancers has continued to accumulate during the last years (Khan et al, 2017). Many studies have confirmed that human exposure to acrylamide may lead to neurological effects in humans (Calleman et al, 1994).…”
Section: Introductionmentioning
confidence: 99%